Comparative Study on the Effects of Lignocaine Nebulization with I/V Lignocaine on Stress Response to Laryngoscopy and Tracheal Intubation - Adnan Ali Baloch, Nazneen Kalim, Altaf Hassan, Vijai Kumar, Zamir Ahmad, Nida Shafqat, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To determine the frequency of any immediate side effects associated with the use of lignocaine in patients. Methodology: Randomized control trial. Sindh Institute of Urology and Transplantation, Karachi from 1st December 2021 to 31st May 2022. Ninety patients enrolled for laryngoscopy and endotracheal intubation. Patients were randomly allocated into three groups on the basis of the treatment. Thirty patients in group I was treated with 2% lignocaine 1.5mg/kg was given by intravenous route, 30 in group N was received 4% lignocaine 1.5mg/kg was given by nebulization and 30 in groups C treated as control group in whom normal saline placebo. The hemodynamic response and side effect was recorded in all patients. Results: The mean heart rate was not statistically significant among groups at baseline and 1 min, 3min to 8 min, while it was statistically significant at 2 min and 9 min among the groups. Mean atrial BP was statistically significant among groups during 2 min to 6 min and then 8 min. regarding immediate side effects, the frequency of side effects were lower in group N and group I than in group C. However, the rate of drowsiness, tremors, and hypoxia was significantly higher in group C compare to group N and group I. Conclusion: Lignocaine is a safe drug and proved to be safe and effective method for the improvement of hemodynamic response to intubation and laryngoscopy. Keywords: Lignocaine, Nebulization of 4%lignocaine, Hemodynamic response, Endotracheal intubation